Petrografía de las areniscas de la sección estratigráfica de bogotá (1971)
The sandstones of the Bogotá stratigraphic section are largely orthoquartzites.  Quartz types include undulose quartz, semi-composite quartz, composite quartz and stretched quartz. Sandstones have undergone a variety of diagenetic alterations. Syndiagenetic changes evident include the formation of quartz grain overgrowths among clean sandstones and the precipitation of carbonate cement.  Anadiagenetic changes include: 1. Ion exchange among clay minerals yielding vermicular kaolinite, illite, sericite, muscovite and chlorite. 2. The recrystallization of carbonate cement or matrix. 3. Continued overgrowth formation or grain replacement by clay minerals, sericite or carbonate following several specific replacement patterns, including a more rapid alteration of polycrystalline quartz types. 4. Formation of complex microstyolitized grain contacts, inclusion trains, comb-like groups of inclusion trains, and fractures in response to increasing grain to grain stress. Epidiagenetic change chiefly Involves the replacement of all matrices, cements, and altered zones by iron oxides. An increase in the amount of detrital matrix inhibits the formation of overgrowths, inclusion trains; comb-like groups of trains and the microstyolitization of grain contacts. Microstyolitization is enhanced by both quartz polycrystallinity and the presence of intergranular illite- sericite.  Among poorly sorted sandstones larger grains take up most of the deformational stress.